'The task of Fort Hare in terms of the Transkei and Ciskei': educational planning at Fort Hare in the 1960's - Beal, M. A. (My University, 1990)
This paper examines government intervention at Fort Hare after 1960. The first part of the paper will examine how the Department of Bantu Education and the new administrators of the college tried to transform Fort Hare into an institution where students were prepared, in terms both of skill and attitude, for a political future in the homelands; the second part of the paper accesses the success of this project, by examining courses of study chosen by students, their pass rates and where graduates were employed.
Paper presented at the Wits History Workshop: Structure and Experience in the Making of Apartheid, 6-10 February, 1990
Keywords: University of Fort Hare History; Apartheid Education policy; Education policy South Africa